Gonadal Steroids and Thyroid Hormones in Non-responding GnRH Treated Poor Libido Breeding Bulls - KUMAR, AJEET; SINGH, JAGIR; HONPARKHE, M; DADARWAL, D; DHALIWAL, G S (The Indian Journal of Animal Reproduction, 2023)
The study was conducted to assess the factors responsible for the no response of GnRH treatment inpoor libido breeding bulls. Eight crossbred (Holstein Friesian x Sahiwal) breeding bulls with the history ofgradual decline in libido over a period of 4-6 months from an organized bull farm in Punjab were selected. Torule out the possibility of physical stressful stimuli which may affect libido, breeding soundness evaluation ofbulls was carried out. All the bulls were given 3 injections of GnRH (Buserelin acetate) in decreasing dose i.e.20μg, 16μg and 12μg at an interval of2 days. Blood samples were collected before treatment and 24 hrs afterevery GnRH injection. Plasma Estradiol (E), Testosterone (T), T3 and T4 were analyzed using MicrowellELISA Kits. Breeding soundness ev.aluation based observations did not reveal any defects in physicalconformation and external or internal genitalia indicating absence of physical stressful stimuli which mayaffect libido. The E to T ratio increased from 6.57 to 44.28 in non responding bulls and decreased from 3.47 to1.70 in responding bulls indicating differential conversion ofT to E following GnRH therapy. Non respondingpoor libido bulls showed decline in T3 to T4 ratio from 90.0 to 64.54. However, T3 to T4 ratio increased from227.65 to 293.36 in treatment responding bulls. It may be concluded that E to T and T3 to T4 ratios play animportant role in modulating the therapeutic response of GnRH. Three injections of GnRH (Receptal,Buserelin)@ 20μg, I 6μg and 12μg at an interval of2 days impro·ved libido in those bulls which had lower E,higher T, T3 and T4 following the GnRH treatment.
Keywords: Gonadal steroids; Thyroid hormones; GnRH; Poor libido bulls